EO 1110 Implementation Team Executive Summary and Recommended Actions
CSUCI's 2018 Strategic Initiatives action item 2. 3 calls for the implementation of a campus-wide approach to meet Executive Order 1110 that will ensure that the curriculum, student support, and placement procedures facilitate student success in first-year placement in written communication and mathematics/quantitative reasoning. The Executive Order supports faculty innovation in curriculum and facilitates an equitable opportunity for first-year students to succeed through existing and redesigned education models. The Executive Order also provides for the continued use of traditional assessment measures as well as the introduction of placement indicators based on the academic performance of students in high school and the Early Start Program.